2013
DOI: 10.1002/clen.201100697
|View full text |Cite
|
Sign up to set email alerts
|

Uptake and Accumulation of Arsenic in Different Organs of Carrot Irrigated with As‐Rich Water

Abstract: Irrigation with arsenic (As)‐rich water in agricultural soil may increase high levels of As in crops and cause food chain contamination. In this study, a greenhouse experiment was established using Spanish agricultural soil (Valladolid and Segovia provinces), that are extensively cultivated for carrot plant, to investigate the process of As uptake, bioaccumulation, and translocation of As from root to shoot and leaves in carrot plant. Arsenic concentrations in different organs of carrot plant, rhizosphere soil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 37 publications
1
6
0
Order By: Relevance
“…Translocation of As to Different Plant Organs Amaranth, green bean, lettuce, spinach, and tomato verified the accumulation trend orders of organs (root > leaf > stem > fruit) described in previous studies (Arslan et al, 2016). Carrot also verified the trend order leaf > root as described by Mayorga et al (2013).…”
Section: Arsenic Concentration In Vegetables Irrigated With As-contaminated Watersupporting
confidence: 83%
See 1 more Smart Citation
“…Translocation of As to Different Plant Organs Amaranth, green bean, lettuce, spinach, and tomato verified the accumulation trend orders of organs (root > leaf > stem > fruit) described in previous studies (Arslan et al, 2016). Carrot also verified the trend order leaf > root as described by Mayorga et al (2013).…”
Section: Arsenic Concentration In Vegetables Irrigated With As-contaminated Watersupporting
confidence: 83%
“…Among the four species where the TF could be calculated, only carrots had a TF > 1. Liu et al (2006) and Mayorga et al (2013) also reported higher concentrations of As in carrot leaves that are described as efficient bio-accumulators.…”
Section: Root Vegetable (Carrot)mentioning
confidence: 90%
“…Arsenic (As) is considered a toxic element to humans, other animals and plants. As a consequence of contamination human health problems have occurred in various countries, often caused by high concentrations of As in the diet, originating from both drinking and irrigation waters, from crops (via soil), vegetables and meat products (Mayorga, Moyano, Anawar, & Garcia-Sanchez, 2013). The detection of As in urine, faeces, skin, hair, nails and lungs has been used as indicators of potential As poisoning.…”
Section: Introductionmentioning
confidence: 99%
“…The uptake and phytotoxicity of the As depends on the levels of phosphate in soil. In the soil particles at low levels of phosphate As can displace phosphate which increases the uptake and phytotoxicity, whereas high levels of phosphate compete with As at root surfaces which results in a decline in uptake and phytotoxicity (Mayorga, Moyano, Anawar, & Garcia-Sanchez, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This is because As applied to irrigation water is primarily accessible to plants for uptake before it is adsorbed on the soil particles. Mayorga et al, 2013 andMarconi et al, 2010 applied lower concentrations of As in the irrigation water (0-150 μg/L and 19-104 μg/L, respectively) and investigated the effect of As-contaminated irrigation water on the As uptake and accumulation in carrot and radish, respectively. Both studies reported an increase in As concentration in the vegetables with an increase in the irrigation water As concentration.…”
Section: The Theme Of the Current Researchmentioning
confidence: 99%